La abdicación del pensamiento ante el horizonte del presente. La inalterable necesidad de un espíritu crítico en filosofía y política - Mansilla, H. C. F. (Nómadas. Critical Journal of Social and Juridical Sciences, 2005)
This essay tries to ascertain the causes of the success of postmodernism as the today prevailing philosophy in Latin America. Properly speaking it is a new authoritarianism, which celebrates certainties about uncertainty. Central points of postmodernism, like the death of the subject and the end of logocentrism, are not believable because postmodernist thinkers produce performative contradictions. They indulge for instance in clear egotism and they spread their theories only by means of logocentric proceedings. In the Latin American area postmodernism has proved to be a new, excluding and intolerant dogma, which has substituted Marxist currents almost without any transition. The literary style of most postmodernist authors has an operatic and diffuse character, which brings about among naive people the impresion of a large erudition and of a praiseworthy plurality.